2012
DOI: 10.1186/1477-9560-10-12
|View full text |Cite
|
Sign up to set email alerts
|

Markers of hypercoagulability in CAD patients. Effects of single aspirin and clopidogrel treatment

Abstract: BackgroundCardiovascular disease with disturbances in the haemostatic system, might lead to thrombotic complications with clinical manifestations like acute myocardial infarction (AMI) and stroke. Activation of the coagulation cascade with subsequent increased thrombin generation, characterizes a prothrombotic phenotype. In the present study we investigated whether prothrombotic markers were associated with risk factors and clinical subgroups in a cohort of patients with angiographically verified coronary arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
(41 reference statements)
4
22
0
1
Order By: Relevance
“…These results suggest that dual antiplatelet therapy is effective in mediating clot microstructure, where patients have lower values of d f corresponding to the production of less densely packed and more porous clots. 4 This study provides further evidence of the potential of d f in monitoring the effects of antiplatelet therapy on clot microstructure formation. 11 The limitations of this study include discrepancy in the numbers collected for both groups.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…These results suggest that dual antiplatelet therapy is effective in mediating clot microstructure, where patients have lower values of d f corresponding to the production of less densely packed and more porous clots. 4 This study provides further evidence of the potential of d f in monitoring the effects of antiplatelet therapy on clot microstructure formation. 11 The limitations of this study include discrepancy in the numbers collected for both groups.…”
Section: Discussionmentioning
confidence: 61%
“…[1][2][3][4] While CAD has been linked to an increased prothrombotic state, no marker has been identified that can accurately assess abnormalities of global haemostasis due to this process and to severity of disease. Identifying a global haemostatic marker of coagulability and fibrinolysis may be important in stratifying risk of atherothrombosis and providing the basis for individualised therapeutic management.…”
Section: Introductionmentioning
confidence: 99%
“…Hypercoagulability resulting from increased coagulation or inhibited fibrinolysis is associated with an increased risk for cardiovascular disease [81, 82]. This is another factor implicated in its association with OSAS [83, 84].…”
Section: Osas and Cardiovascular Diseases Mechanismsmentioning
confidence: 99%
“…Thrombin converts soluble fibrinogen to insoluble fibrin strands and form blood clots [911]. Previous studies have shown that coagulation factors have an essential role in advancing atherosclerosis and CAD [12–14]. High levels of FVII coagulant activity (FVIIc) and fibrinogen have been found to be significantly associated with increased risk of coronary events [15].…”
Section: Introductionmentioning
confidence: 99%